ANALISIS KEPUASAN NASABAH BPR KERTA RAHARJA MELALUI KUALITAS CUSTOMER SERVICE. - Shopia Rahmi; Nur Azizah; Anggi Agatha; Desy Nuraminah (LPPM Politeknik Pajajaran ICB Bandung, 2026)
This study examines the quality of customer service in improving customer satisfaction at BPR Kerta Raharja. High-quality service is an essential factor for banks to maintain customer trust, loyalty, and attract new customers. The study aims to analyze the influence of customer service quality on customer satisfaction. A qualitative research method was employed, with data collected through questionnaires based on service quality indicators and direct field observations. The findings indicate that customer service at BPR Kerta Raharja has been implemented effectively by providing prompt, accurate, courteous, and reliable services in accordance with the bank’s standard operating procedures. The dimensions of reliability, responsiveness, assurance, empathy, and trust significantly contribute to customer satisfaction. Excellent customer service is able to meet customers’ needs and expectations, resulting in higher levels of satisfaction, stronger customer loyalty, and a positive corporate image for BPR Kerta Raharja as a financial institution committed to delivering excellent banking services.